2014
DOI: 10.1109/tcbb.2014.2326860
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling and Evaluation of Novel Dibenzopyrrole Derivatives as Telomerase Inhibitors and Potential Drug for Cancer Therapy

Abstract: During previous years, many studies on synthesis, as well as on anti-tumor, anti-inflammatory and anti-bacterial activities of the pyrazole derivatives have been described. Certain pyrazole derivatives exhibit important pharmacological activities and have proved to be useful template in drug research. Considering importance of pyrazole template, in current work the series of novel inhibitors were designed by replacing central ring of acridine with pyrazole ring. These heterocyclic compounds were proposed as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…Carbazole derivatives bearing diamine groups presented a new potential for telomerase inhibition. Using three different docking programs (CDOCKER, Ligandfit, Autodock) and interaction analysis demonstrated that compounds 14a and 14b (Figure 20) had the best telomerase inhibition activity more interestingly with the introduction of a pyrazole ring 48 .…”
Section: Carbazole-36-diamine Derivativesmentioning
confidence: 99%
“…Carbazole derivatives bearing diamine groups presented a new potential for telomerase inhibition. Using three different docking programs (CDOCKER, Ligandfit, Autodock) and interaction analysis demonstrated that compounds 14a and 14b (Figure 20) had the best telomerase inhibition activity more interestingly with the introduction of a pyrazole ring 48 .…”
Section: Carbazole-36-diamine Derivativesmentioning
confidence: 99%
“…19 provided the first structural model of human telomerase, using computational methods derived from the X-ray structure of the full-length T.castaneum telomerase (PDB: 3DU6; apo form) 11 and the enzyme in complex with a RNA∶DNA hairpin (PDB: 3KYL) 32 . In the present study, we used the TERT catalytic subunit of the human telomerase model 19 and defined/predicted the active-site residues based on T. castaneum telomerase structure 11,3335 (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…1A) 19 .
Figure 1( A ) The structure of the catalytic subunit (TERT) and active-site residues in Tribolium castaneum (PDB: 3DU6) 11 and the human 19 telomerase model. ( B ) The structure of ligand molecules, namely, C_9i 33 , C_9k 33 , 16A 34 , and NSC749234 36 , which were selected to study with human telomerase.
…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations